2021
DOI: 10.1002/cpdd.907
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic and Pharmacodynamic Target Attainment in Adult and Pediatric Patients Following Administration of Ceftaroline Fosamil as a 5‐Minute Infusion

Abstract: The key pharmacokinetic/pharmacodynamic (PK/PD) efficacy index for β‐lactam antibiotics is the percentage of time that free drug concentrations exceed the minimum inhibitory concentration (MIC) of bacteria during each dosing interval (fT>MIC). Ceftaroline fosamil, the prodrug of the β‐lactam ceftaroline, was initially approved for administration as 60‐minute intravenous (IV) infusions. Population PK analyses comparing exposure and PK/PD target attainment for 5‐minute and 60‐minute IV infusions, described here,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Since it can be challenging to conduct large-scale efficacy trials in pediatric populations, extrapolation approaches combining observed PK and safety data in children with adult efficacy and safety data and population PK modeling/simulation and PTA analysis are accepted techniques to support antibiotic dose selection and approval in pediatric drug development [ 56 – 59 ]. Using the updated PK/PD targets described above, population PK modeling and simulations have shown that standard ceftaroline fosamil adult and pediatric doses provide high (> 90%) PTA across all age groups against target pathogens at their respective EUCAST and CLSI susceptible MIC breakpoints [ 53 , 60 ].…”
Section: Ceftaroline Fosamil Dosing and Breakpointsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since it can be challenging to conduct large-scale efficacy trials in pediatric populations, extrapolation approaches combining observed PK and safety data in children with adult efficacy and safety data and population PK modeling/simulation and PTA analysis are accepted techniques to support antibiotic dose selection and approval in pediatric drug development [ 56 – 59 ]. Using the updated PK/PD targets described above, population PK modeling and simulations have shown that standard ceftaroline fosamil adult and pediatric doses provide high (> 90%) PTA across all age groups against target pathogens at their respective EUCAST and CLSI susceptible MIC breakpoints [ 53 , 60 ].…”
Section: Ceftaroline Fosamil Dosing and Breakpointsmentioning
confidence: 99%
“…The addition of pediatric dosing recommendations in the European and US labels was based on completion of the PIP and fulfillment of PREA requirements, which included clinical trials in relevant pediatric indications and population PK analyses [ 60 , 65 ]. In the case of the European label, the pediatric population PK analyses used the PK/PD targets described by Das et al [ 53 ], with these analyses demonstrating drug exposures and PTA in pediatric patients equivalent to adults with normal renal function receiving standard and high ceftaroline fosamil doses.…”
Section: Ceftaroline Fosamil Dosing and Breakpointsmentioning
confidence: 99%
See 1 more Smart Citation
“…After 12 h post-injection, ceftaroline was eliminated from the blood compartment, and the area under the concentration-time curve from 0 to 24 h (AUC 0–24 ) was 49.5 µg.h/mL (considering a twice daily regimen was applied). Thus, the C max achieved in the rat was similar to the C max reported in humans (20.8 µg/mL on average following a 600 mg/12 h administration)( 24 ) but the AUC in the rat was approximately half the AUC obtained in humans (97.5 µg.h/mL on average), and the % T >MIC was, therefore, about 40% in the rat, based on an MIC of 0.5 µg/mL for the MRSE strain used in this study ( 25 ).…”
Section: Resultsmentioning
confidence: 59%
“…Ceftaroline clearance is significantly affected by age, renal function or the presence of infection [ 14 ]. As a beta-lactam antimicrobial, the pharmacokinetic/pharmacodynamic (PK/PD) index that better correlates with efficacy is the time, expressed as the percentage of the dosing interval by which free drug concentration is over the minimum inhibitory concentration (MIC) of the bacteria responsible for the infection (% f T >MIC ) [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%